The feminism and visual culture reader - Jones, Amelia (Routledge, 2010)
Feminism is one of the most important perspectives from which visual culture has been theorized and historicized over the past forty years. Challenging the notion of feminism as a unified discourse, this second edition of The Feminism and Visual Culture Reader assembles a wide array of writings that address art, film, architecture, popular culture, new media and other visual fields from a feminist perspective. The essays, 40% of which are new to the second edition, are informed by the authors’ deep attention to historical, geographical, and disciplinary contexts as well as by cutting edge concerns such as globalization, diasporic cultural shifts, developments in new media technologies, and intersectional identity politics. The Feminism and Visual Culture Reader combines classic texts with six specially commissioned pieces, all by leading feminist critics, historians, theorists, artists, and activists. Articles are grouped into thematic sections, each of which is introduced by the editor. Providing a framework within which to understand the shifts in feminist thinking in visual studies, as well as an overview of major feminist theories of the visual, this reader also explores how issues of race, class, nationality, and sexuality enter into debates about feminism in the field of the visual
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; arts visuels et médiatiques; cours; discipline; discours dominant; fem1000; genre; har4600; identités LGBTQIA2+; interdisciplinarité; intersectionnalité; premier cycle; périodes historiques; racialisation; sexualité; systèmes d'oppressions; thématiques; théories féministes; études culturelles

Brain storm: The flaws in the science of sex differences - Jordan-Young, Rebecca M. (Harvard University Press, 2010)
Jordan-Young has written a stunning book that demolishes most of the science associated with the dominant paradigm of the development of sex and gender identity, behavior, and orientation. The current paradigm, brain organization theory, proposes: "Because of early exposure to different sex hormones, males and females have different brains"; and these hormones also create "gay" and "straight" brains. Jordan-Young interviewed virtually every major researcher in the field and reviewed hundreds of published scientific papers. Her conclusion: "Brain organization theory is little more than an elaboration of longstanding folk tales about antagonistic male and female essences and how they connect to antagonistic male and female natures." She explains, in exquisite detail, the flaws in the underlying science, from experimental designs that make no statistical sense to "conceptually sloppy" definitions of male and female sexuality, contradictory results, and the social construction of normality. Her conclusion that the patterns we see are far more complicated than previously believed and due to a wider range of variables will shake up the research community and alter public perception.
Keywords: LGBTQIA2+; analyse critique; approches et analyses; corps; cours; différence des sexes; discipline; discours dominant; identité sexuelle; identités LGBTQIA2+; neurosciences; premier cycle; psy4910; psychologie; revue de la littérature; sciences; sciences humaines; sexe/genre; sexisme; sociologie; systèmes d'oppressions; thématiques

« Penser le sexe » dans Surveiller et jouir: anthropologie politique du sexe - Rubin, Gayle; Bolter, Flora; Broqua, Christophe; Mathieu, Nicole-Claude; Mesli, Rostom (Surveiller et jouir: anthropologie politique du sexe, 2010)
Chérir, plutôt qu'éradiquer la diversité des pratiques sexuelles, tel est le programme d'une théorie politique radicale de la sexualité selon Gayle Rubin. Sa mise en oeuvre s'est heurtée à la volonté permanente d'imposer une bonne sexualité : hétérosexuelle, monogame, conjugale, gratuite, intragénérationnelle, génitale, à deux, procréative, sans sex toys ni usage de pornographie. Gayle Rubin, féministe et lesbienne militante, est ainsi devenue la cible de la droite états-unienne comme de pans entiers des mouvements féministes et lesbiens. Écrivant sous forme d'articles clairs et décisifs, elle a ouvert la voie au développement d'outils d'analyse spécifiques pour comprendre les oppressions matérielles et symboliques subies par les hors-la-loi du sexe et a contribué à la fondation de la théorie féministe, des études de genre et de la théorie queer. Les réflexions de Michel Foucault sur l'éthique du sadomasochisme masculin se trouvent ici éclairées par celle qu'il appelle « notre amie Gayle Rubin »
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; discours dominant; europe; france; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexualité; soc3113; sociologie; systèmes d'oppressions; thématiques